2022
DOI: 10.1161/circheartfailure.121.009238
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Adipose Tissue and Outcome in Heart Failure With Mid-Range and Preserved Ejection Fraction

Abstract: Background: Epicardial adipose tissue (EAT) accumulation is thought to play a role in the pathophysiology of heart failure (HF) with mid-range and preserved ejection fraction, but its effect on outcome is unknown. We evaluated the prognostic value of EAT volume measured with cardiac magnetic resonance in patients with HF with mid-range ejection fraction and HF with preserved ejection fraction. Methods: Patients enrolled in a prospective multicenter stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…However, some longitudinal studies have shown that higher EAT at baseline is associated with new‐onset HFpEF, 6,30 as well as a worse prognosis in those with established HFpEF, 7 independent of overall obesity and important comorbidities. An overview of the recent studies that investigated EAT in relation to HFpEF is shown in Table 1 6,7,23,25–27,30–41 . Of note, one study by Haykowsky et al 32 .…”
Section: Epicardial Adipose Tissue and Hfpefmentioning
confidence: 99%
“…However, some longitudinal studies have shown that higher EAT at baseline is associated with new‐onset HFpEF, 6,30 as well as a worse prognosis in those with established HFpEF, 7 independent of overall obesity and important comorbidities. An overview of the recent studies that investigated EAT in relation to HFpEF is shown in Table 1 6,7,23,25–27,30–41 . Of note, one study by Haykowsky et al 32 .…”
Section: Epicardial Adipose Tissue and Hfpefmentioning
confidence: 99%
“…Epicardial fat accumulation is a risk of HF with mildly reduced ejection fraction (HFmrEF) and HF preserved ejection fraction (HFpEF). In these patients, a high epicardial fat volume is also a predictor of death and/or hospitalization for HF [ 147 ]. Greater total EATs in HFpEF is associated with myocardial fibrosis markers but not in HFrEF [ 148 ].…”
Section: Physiopathological Mechanismsmentioning
confidence: 99%
“…Unfortunately, the current study by Obokata et al did not include cardiac MRI scanning to further bolster their findings. Recent cardiac MRI studies in patients with HFpEF have already demonstrated that the site of EAT accumulation is associated with structural changes that induce haemodynamic and electrical changes, 11 and that in these patients higher EAT volume is associated with worse outcomes, including all‐cause mortality and HF hospitalizations 12 …”
Section: Figurementioning
confidence: 99%
“…Recent cardiac MRI studies in patients with HFpEF have already demonstrated that the site of EAT accumulation is associated with structural changes that induce haemodynamic and electrical changes, 11 and that in these patients higher EAT volume is associated with worse outcomes, including all-cause mortality and HF hospitalizations. 12 We therefore hypothesize that, apart from local proinflammatory and pro-fibrotic changes due to increased EAT volumes, build-up of EAT itself may also act as an important disease modifier that increasing volumes of EAT may form a dense . and compact layer around the myocardium that prevents the heart from passive filling, resulting in higher intracardiac pressures and lower natriuretic peptide levels due to limited left ventricular (and right ventricular) stretch, and thus uncoupling of intracavitary and intravascular pressures.…”
mentioning
confidence: 99%